Language Policy and National Feeling in Context Ukraine’s Euromaidan, 2014-2016 - Fedinec Csilla; Фединець Чілла; Csernicskó István; Черничко Степан; Csernicsko Istvan (Silesian University in Opava, Faculty of Public Policies, 2017)
Abstract. Ukraine is the best example of "nationalizing" nationalism. During its twenty-fi ve year old existence the language question – in addition to historical approach and ethnical identity – has belonged to the unclosed questions of personal and group identity, and represents one of the central themes of political struggle. Offi cial Ukrainian language policy permanently wants to promote the use of Ukrainian or Russian by overshadowing one or the other. Measures regulating language use have never been consequently applied, which fact in itself is enough to represent a permanent subject for political campaigns. Political powers unable to solve actual economic and social problems wanted to distract attention by this means. That is why the politicized language question could contribute to the political crisis and the outbreak of the armed confl ict at the end of 2013 and at the beginning of 2014 in a politically unstable country facing economic breakdown. The present paper examines the role of the language question in the Ukrainian crisis in the period of 2014–2016.
Keywords: Ukraine; Euromaidan; crisis; national identity; language policy